How do banks interact with fintech startups? - Lars Hornuf; Milan F. Klus; Todor S. Lohwasser; Armin Schwienbacher (Small Business Economics, 2020)
The increasing pervasiveness of technology-driven firms that offer financial services has led to growing pressure on traditional banks to modernize their core business activities and services. Many banks tackle the challenges of digitalization by cooperating with startup firms that offer technology-driven financial services and novel service packages (fintechs). In this article, we examine which banks typically collaborate with fintechs, how intensely they do so, and which form of alliance they prefer. Using hand-collected data covering the largest banks from Canada, France, Germany, and the United Kingdom, we provide detailed evidence on the different forms of alliances occurring in practice. We show that banks are significantly more likely to form alliances with fintechs when they pursue a well-defined digital strategy and/or employ a chief digital officer. Moreover, in line with incomplete contract theory, we find that banks more frequently invest in small fintechs but often build product-related collaborations with larger fintechs.
Keywords: G21; G23; G34; M13; L26; 330; Fintech; Strategic alliance; Make; buy; or ally; Entrepreneurial finance; Banks